A strange counterpoint : classical music performance and identities in Grahamstown, South Africa - Marais, Terence Wilmot Eugene (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2011)
This study investigates the perceptions of South African practitioners of Western European Art Music (WEAM), specifically as they relate to the value of WEAM in contemporary South African society. In exploring some of the connections between musical identity and national identity, it sets out to discover what value WEAM holds for a certain group of student pianists. Qualitative empirical data was collected in the form of in-depth, semi-structured interviews and questionnaire responses, and the findings point to numerous, nuanced expressions of self and varied intersections of the nation with musical identity in the life of the individual. Further, WEAM appears to represent a crucial point of identification for these individuals, in each case generating positive affirmations of the self.
Keywords: Music -- Western influences; Music -- Performance -- Psychological aspects; Music appreciation -- South Africa -- Grahamstown; Music -- South Africa -- Grahamstown